How to provide consultant peer support – the south coast new consultants group. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Ford-Dunn, Suzanne; Barclay, David
Abstract : Introduction: Peer support is identified though the NHS appraisal process and national bodies such as Royal Colleges, as being essential for the on-going wellbeing and professional development of consultants. It is recognised that the early years as a consultant can be particularly stressful and that palliative medicine consultants have difficulty obtaining peer support since many work in isolation. We identified a lack of peer support within our area. Description: A new consultants group was formed in 2009, using loose geographical boundaries of the Sussex Cancer Network – involving 10 'new or soon to be' consultants. The group meets 4 times per year, topics relevant to new consultants are agreed and organising each meeting is shared. Meetings either have invited external speakers or are run by one of the members. The meetings aim to provide CPD (topics include Commissioning, managing CNS's in difficulty, writing a business case etc) but also to provide members with time to discuss any issues that have arisen, clinical or non-clinical. The group is cost effective in that SPA time is used for the meeting, with costs for speakers/meeting rooms etc covered by sponsorship if needed. Benefits: Consultants in isolated posts have found the peer support invaluable. Feedback from members is highly positive – further evaluation is underway to produce data to support its effectiveness. The presence of our group has been used by local units to enhance the attractiveness of new consultant posts. Future plans: As some members reach the end of their first 5 years in post, and Consultant vacancies in the area are filled, debate is occurring as to the terms of reference of the group. The support has been so effective it is proposed to continue meeting, but extending membership to become a generic doctors' professional development meeting.